Optimized Manufacturing Layout and Operational Balancing - A Case Study in an Electronic Line from the Industrial Pole of Manaus/AM, to increase productivity - Silva Figueira, Raimundo Wenderson da; Pinto, Fabiana Rocha (International Journal of Advanced Engineering Research and Science, 2021)
In the face of an extremely complicated phase for the national and international market, the factories are seeking ways to survive this turbulent moment for the economy, pursuing alternatives in order to make their processes more sustainable. So, in this way this can be possible to remain in the midst of increasingly difficult challenges and goals, it is understood the great importance of seeking the optimization of its manufacturing processes through their layouts in order to be economically stronger. Based on this, a case study was recommended to carry out an experiment, whose main objective is to optimize the layout as well as every part that makes up its production processes, proposing the unification of two production lines installed in the PIM (Manaus Industrial Pole) of the Electronics sector. With information of the production process through the collected data, was identified in the first layout the excesses in two production lines under study, which had the two identical processes in common, as well as the duplication of stations, tests and the unbalance of operational activities in oversized stream. The update of Takt time was also necessary given the opportunities found specifically in the packing area, with overproduction waste in certain stations. Searching for more productivity and improvements at a low cost, was determinate to choose the study to optimize the layout and improvements in the flow with a reduction in the operational cost through low-cost means. The entire experiment was accomplished with tools and programs in free versions available on the internet and already widely used in the industrial factory and environments, such as Sketchup, GBO (Operational Balance Chart) and Kinovea video editing program.